Bimodal ERCP, a new way of seeing things - Reuterwall, Marcus; Waldthaler, Alexander; Lubbe, Jeanne; Kadesjö, Nils; Pozzi Mucelli, Raffaella; Del Chiaro, Marco; Lohr, Matthias; Arnelo, Urban (Endoscopy International Open, 2020)
Background and study aims Conventional endoscopic retrograde cholangiopancreatography (ERCP) is hampered by two-dimensional visualization, post-procedural adverse events (AEs), and exposure to ionizing radiation. Bimodal ERCP might mitigate these challenges, but no reports of its use are available to date. The aim of this study was to explore the feasibility of bimodal ERCP, while investigating its potential clinical yield. Patients and methods This was a retrospective observational study of patients that underwent bimodal ERCP in a single tertiary academic referral center. Thirteen patients undergoing conventional ERCP had a previously T2-weighted isotropic 3 D TSE MRCP sequence aligned and fused with the two-dimensional image generated from the fluoroscopy c-arm unit in real time. Results Over a 2-month period, 13 patients with a mean age of 54 underwent bimodal ERCP for bile duct stricture (61.5 %), complex cholelithiasis (7.7 %) and ductal leakage (30.1 %). Bimodal ERCP was feasible in all 13 cases, and image quality was assessed as “good” in 11 patients (84.6 %). Bimodal ERCP aided in visualizing the lesion of interest (76.9 %), assisted in understanding the 3 D anatomy of the biliopancreatic ductal system (61.5 %), and aided in finding a favorable position for the c-arm (38.4 %) for subsequent therapeutic intervention. Conclusions This first report on bimodal ERCP proves its feasibility and suggests that it may assist in increasing both the diagnostic and therapeutic yield of ERCP, while at the same time decreasing AEs during and after ERCP. Its main application might lie in treatment of complex intrahepatic disease.